Microbiological insight into various underground gas storages in Vienna Basin focusing on methanogenic Archaea - Hanišáková, Nikola; Vítězová, Monika; Vítěz, Tomáš; Kushkevych, Ivan; Kotrlová, Eva; Novák, David; Lochman, Jan; Zavada, Roman (Frontiers in Microbiology, 2023)
In recent years, there has been a growing interest in extending the potential of underground gas storage (UGS) facilities to hydrogen and carbon dioxide storage. However, this transition to hydrogen storage raises concerns regarding potential microbial reactions, which could convert hydrogen into methane. It is crucial to gain a comprehensive understanding of the microbial communities within any UGS facilities designated for hydrogen storage. In this study, underground water samples and water samples from surface technologies from 7 different UGS objects located in the Vienna Basin were studied using both molecular biology methods and cultivation methods. Results from 16S rRNA sequencing revealed that the proportion of archaea in the groundwater samples ranged from 20% to 58%, with methanogens being the predominant. Some water samples collected from surface technologies contained up to 87% of methanogens. Various species of methanogens were isolated from individual wells, including Methanobacterium sp., Methanocalculus sp., Methanolobus sp. or Methanosarcina sp. We also examined water samples for the presence of sulfate-reducing bacteria known to be involved in microbially induced corrosion and identified species of the genus Desulfovibrio in the samples. In the second part of our study, we contextualized our data by comparing it to available sequencing data from terrestrial subsurface environments worldwide. This allowed us to discern patterns and correlations between different types of underground samples based on environmental conditions. Our findings reveal presence of methanogens in all analysed groups of underground samples, which suggests the possibility of unintended microbial hydrogen-to-methane conversion and the associated financial losses. Nevertheless, the prevalence of methanogens in our results also highlights the potential of the UGS environment, which can be effectively leveraged as a bioreactor for the conversion of hydrogen into methane, particularly in the context of Power-to-Methane technology.